2016
DOI: 10.1177/0261927x16663591
|View full text |Cite
|
Sign up to set email alerts
|

The Language of Dementia Science and the Science of Dementia Language

Abstract: The language of dementia science and the science of dementia language: linguistic interpretations of an interdisciplinary research field. AbstractLanguage is a balance of precision and flexibility, and scientific dialogue across disciplines faces challenges in how terms are used and how phenomena, including language itself, are described and explained. Taking dementia as its focus, this paper offers linguistic perspectives on causes of inherent difficulty with terminological exactness. Attention is paid to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Using TDM, we analyzed key term frequency within 20,000 representative AMR articles to determine consistent, and at times inconsistent, language use within articles categorized into four independent term bins (Human, Animal, Environmental, and One Health bins). As language use is key to interdisciplinary group dynamics, terminological imprecision can result in dissimilar vocabulary that presents a barrier to moving to the shared cognition required for strategic interdisciplinary problem solving [ 19 , 25 , 27 , 28 , 29 , 30 ], particularly as it relates to AMR [ 24 ]. We identified that when using a consistent search term string, the key term usage deviated amongst the individual domains, with search term clusters shown within each bin ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Using TDM, we analyzed key term frequency within 20,000 representative AMR articles to determine consistent, and at times inconsistent, language use within articles categorized into four independent term bins (Human, Animal, Environmental, and One Health bins). As language use is key to interdisciplinary group dynamics, terminological imprecision can result in dissimilar vocabulary that presents a barrier to moving to the shared cognition required for strategic interdisciplinary problem solving [ 19 , 25 , 27 , 28 , 29 , 30 ], particularly as it relates to AMR [ 24 ]. We identified that when using a consistent search term string, the key term usage deviated amongst the individual domains, with search term clusters shown within each bin ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Language and stories about dementia in film, theatre, literature, and documentaries contribute to the social and cultural constructions of dementia and reinforce these in popular consciousness (Zelig, 2014). Language is also recognised as important in clinical approaches to dementia (Wray, 2017), but is seen as an important aspect of participative and inclusive research (Waite et al, 2019). In our earlier research concerning daily practices, we noted how the containment, care, holding, and containing practices demarcated the problematic ‘other’ from those working in care-giving or ‘containment’ positions.…”
Section: (Global) Social Problem Constructionmentioning
confidence: 99%
“…Physical activity promotion connects different health professionals and is often interdisciplinary, ranging from medical personnel to social workers. The differentconceptualizations of expertise guiding these promotion activities sometimes generate some pitfalls (Wray, 2017). The changing language of lay older persons adds further complications.…”
Section: Introductionmentioning
confidence: 99%